2019
DOI: 10.32479/irmm.7541
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Shopping Experience and Perceived Value Toward Customer Satisfaction and Their Impacts on Customer Loyalty at Minimarkets in Aceh

Abstract: The aim of this research is to identify: (1) the influence of shopping experience and the perceived value toward customersatisfaction (2) the influence of shopping experience, the perceived value and customersatisfaction toward customer loyalty (3) the indirect influence of shopping experience and perceived value toward customer loyalty at minimarkets in Aceh evaluated through customer satisfaction.The research was conducted at minimarkets in Aceh. The objects of the study are: Shopping experience role, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…< 0.05 (Ndangi et al, 2019). Based on the results of the f test, Social Media, Wort of Mouth, and Brand Image simultaneously have an effect on the increase in Home Sales of the Tempe Industry in terms of the calculated f value of 542,310 > from f table 2.70 (Amri et al, 2019). Based on the R-Square of 0.944, the value of the contribution of the impact of Social Media, Wort of Mouth, Brand Image simultaneously has an effect on the increase in Home Sales of the Tempe Industry by 94.4% and the remaining 5.6% is influenced by other factors outside of this study (Ningsih & Dukalang, 2019)…”
Section: T Testmentioning
confidence: 98%
“…< 0.05 (Ndangi et al, 2019). Based on the results of the f test, Social Media, Wort of Mouth, and Brand Image simultaneously have an effect on the increase in Home Sales of the Tempe Industry in terms of the calculated f value of 542,310 > from f table 2.70 (Amri et al, 2019). Based on the R-Square of 0.944, the value of the contribution of the impact of Social Media, Wort of Mouth, Brand Image simultaneously has an effect on the increase in Home Sales of the Tempe Industry by 94.4% and the remaining 5.6% is influenced by other factors outside of this study (Ningsih & Dukalang, 2019)…”
Section: T Testmentioning
confidence: 98%
“…The sampling method used accidental sampling, which is sampling by chance. The method is part of the non-probability sampling, namely there are no certain criteria in sampling so that all samples have the same opportunity (Amri et al, 2019) .…”
Section: Samplesmentioning
confidence: 99%
“…The data analysis method used is simple linear regression analysis, and hypothesis testing with t-test (partial), simultaneous test (ANOVA) and coefficient of determination (R Square). According to Imam Ghozali (Amri et al, 2019), the provisions in making decisions for the t test are if the Sig value is less than 0.05 and the t count is greater than the t table, it can be said to be influential and significant. Simultaneous f-test is based on Sig value less than 0.05 and f-count is greater than f-table.…”
Section: Sampling Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown evidence that perceived value has a more significant effect on customer loyalty than other variables such as trust and commitment (Chen, 2012). In addition, various studies show that perceived value has a significant effect on customer loyalty (Amri, Ma'ruf, Tabrani, & Darsono, 2019;Hamouda, 2019;Scridon, Achim, Pintea, & Gavriletea, 2019). The relationship between perceived value and loyalty is very dynamic and needs to be studied empirically (El-Adly & Eid, 2016).…”
Section: Introductionmentioning
confidence: 99%